ANISE YIELD AND YIELD COMPONENTS WITH VARYING SOWING DATES, PLANT DENSITIES, AND NITROGEN FERTILIZERS IN SULAIMANI REGION- IRAQ - Ahmed, Kazhal R.; Ahmed, R. M.; Rasul, A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
To improve both the quantity and quality of anise (Pimpinella anisum L.) seeds, a field experiment was conducted in the fall season of 2021-2022 at two locations: Qlyasan Agricultural Research Station and Kanipanka Research Station. The experiment was designed as factorial experiments (2×2×3) within Randomized Complete Block Design (RCBD) using 3 replicates, the first factor was two sowing dates (20th Oct. and 20th Nov), the second factor was plant density (50 and 100 plants m-2), and the third factor was the application of Nitrogen (15 and 30 kg ha-1 as well as control). The mean results of the both locations indicated that the highest seed yield of 2759 kg ha-1 gained by the combination of the Oct. 20 sowing date within 100 plants m-2 density and the application of 30 kg ha-1 as urea 46% nitrogen, while the highest essential oil yield of 31 kg ha-1 occurred with the combination of the sowing date of Oct. 20 with 100 plants m-2 and 15 Kg ha-1 nitrogen. The Kanipanka location outperformed the Qlyasan location by 91.50% and 46.60% for the characters' seeds yield and essential oil yield, respectively.